A Synchronous Tuning Control System for Very Low Frequency Communication Based on Real-Time Impedance Detection - Shize Wei; Xu Xie; Yuqing Liu; Hao Zuo (Applied Sciences)
A Very Low Frequency (VLF) communication system is a communication system with limited transmit bandwidth, mainly because the VLF antenna is a high-Q electrically small antenna (ESA) with a narrow effective bandwidth, which limits the improvement of communication rate. To achieve broadband VLF communication, the commonly used method is synchronous tuning technology. In this paper, a synchronous control algorithm based on real-time impedance detection and a synchronous control system structure are proposed. Simulation results show that the method can improve the antenna matching performance, increase the effective bandwidth of the antenna feeder system, and improve the signaling rate.